The cost effectiveness of a low clearance nephrology care - Guedes,Anabela Malho (2015)
Background: The projected growth in spending for the treatment of end-stage renal failure threatens to become unsustainable for most countries. Different sources suggest that patients with progressive chronic kidney disease should be managed in a multidisciplinary care setting. Given that multidisciplinary teams impact on health care resources, it is imperative to evaluate their effectiveness. The purpose of this study was to evaluate the impact of exposure to conventional nephrology care or low clearance nephrology care (LCC) prior to dialysis initiation on patient outcomes and expenditure after dialysis initiation. Methods: This study considered incident haemodialysis patients attending the LCC vs. receiving standard nephrologist care at our Centre, between 2008 and 2011. Costs were calculated based on the Portuguese capitation system introduced in 2008. Results: During the evaluation period, 176 patients initiated dialysis, 113 exposed to the LCC and 63 received standard nephrologist care. There were no demographic differences between groups. The LCC group started dialysis with higher eGFR (10.1 vs. 8.3 ml/min/1.73m2, p = 0.002), higher albumin (3.8 vs. 3.5 g/dl, p = 0.020), lower PTH (549.7 vs. 841.1 pg/ml, p = 0.008); in this group, a higher proportion of patients started dialysis with a definitive vascular access (85.8% vs. 65.5%, p = 0.002). The biochemical parameters were comparable after 6 and 12 months, but the costs to achieve the same analytical objective were much lower in the LCC group: 3737.7 vs. 5087.3 euros (p = 0.005) and 6336.4 vs. 8024.6 euros (p = 0.035) after 6 and 12 months, respectively. There were no differences in survival or morbidity between groups. Older age was associated with greater risk of hospitalization (p = 0.032) and death (p < 0.001); a definitive vascular access correlated with lower hospitalization (p = 0.006) and a trend to lower risk of death (p = 0.051). Conclusions: Better biochemical variables and presence of a definitive vascular access at dialysis initiation in the LCC, resulted in a lower expenditure during the first year of haemodialysis